Indonesian-English Code-Switching in Contemporary Contexts: Insights from 2023–2024 Data - Akfan, Sofyan Sukwara (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2025)
Code-switching, prevalent in multilingual contexts, exemplifies linguistic adaptability and social conformity. This study employed a qualitative research design utilizing content analysis methods, involving randomly selected participants and unstructured interviews to investigate Indonesian-English code-switching on social media platforms, particularly Facebook. The data underwent evaluation in three phases: reduction, display, and conclusion formulation. The results identified three main types of code-switching: intra-sentential (50%), inter-sentential (30%), and tag-switching (20%). Intra-sentential switching was the predominant form of code-switching, indicating a high degree of integration between the two languages in informal online conversation. Individuals swap codes for various reasons: to display their status or "cool" persona (60%), to showcase their educational background (24%), and to attract attention (16%). Code-switching functions both as communication and a marker of identity, with English often symbolizing prestige among youth. It supports adaptability, problem-solving, and inclusivity in education but, when excessive especially intra-sentential may reduce long-term proficiency. Overall, it reflects globalization’s influence on language and identity in multilingual cultures.